How do types of employment relate to health indicators? Findings from the Second European Survey on Working Conditions. Issue 7 (1st July 2000) - Benavides, F G; Benach, J; Diez-Roux, A V; Roman, C
Abstract : STUDY OBJECTIVE: To investigate the associations of various types of employment with six self reported health indicators, taking into account the part played by demographic variables, individual working conditions and four ecological indicators at the country level. DESIGN: Cross sectional survey (structured interview) of a sample of the active population of 15 European countries aged 15 years or over. Main independent variables were nine types of employment categorised as follows: small employers, full and part time permanent employees, full and part time fixed term employees, full and part time sole traders and full and part time temporary contracts. Main outcome measures were three self reported health related outcomes (job satisfaction, health related absenteeism, and stress) and three self reported health problems (overall fatigue, backache, and muscular pains). Logistic regression and multilevel models were used in the analyses. SETTING: 15 countries of the European Union. PARTICIPANTS: 15 146 employed persons aged 15 or over. MAIN RESULTS: Precarious employment was consistently and positively associated with job dissatisfaction but negatively associated with absenteeism and stress (as compared with full time permanent workers). Fatigue, backache and muscular pains also tended to be positively associated with precarious employment, particularly with full time precarious employment. Small employers reported high percentages of stress and fatigue, but absenteeism was relatively low. Sole traders generally reported high percentages of all outcomes, except for absenteeism, which was low. For each type of employment (except temporary contracts), full time workers tended to report worse health outcomes than part time workers. Patterns were generally consistent across countries. Associations persisted after adjustment for individual level working conditions and were not modified by country level variables. CONCLUSIONS: This study is the first to examine the relations between various types of employment and six health related indicators for all 15 member states of the European Union. Suggestive patterns worthy of further exploration have been found. Standardised definitions of types of underemployment and health related outcomes, more potent epidemiological designs and the inclusion of socioeconomic information (for example, social security systems, incapacity benefit schemes) at the regional level are proposed for inclusion in further research.